Nephronectin and the genetics of lung function variability - Qian, Guoqing (2023)
Genetic variation at the chromosome 4 locus containing the gene nephronectin (NPNT) is strongly associated with both lung function variability and the risk of developing chronic obstructive pulmonary disease (COPD) in genome wide association studies (GWAS). NPNT is a conserved extracellular matrix protein, which appears to play a crucial role in regulating cell proliferation, differentiation and adhesion. The main aims of the thesis were to i) to investigate the profile of NPNT in different airway structural cell lines and lung tissues; ii) to identify the contribution of targeting NPNT by two approaches (RNA interference, or CRISPR/Cas9) to determine differentially expressed genes and potential pathways involved in human bronchial epithelial cell homeostasis; and iii) to assess the potential for serum NPNT protein levels to be used as a biomarker in either stable COPD stable or patients with exacerbations.